2019
DOI: 10.1016/j.jsha.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ knowledge and practice attitudes toward infective endocarditis antibiotic prophylaxis guidelines in Saudi Arabia

Abstract: ObjectivesTo assess the physicians’ knowledge and practice attitudes toward the infective endocarditis antibiotics prophylaxis guidelines in Saudi Arabia. Moreover, to determine whether there is knowledge-to-practice discrepancy.MethodsA cross-sectional study was performed using a self-administered questionnaire. A questionnaire was distributed among physicians dealing with congenital heart disease patients in Saudi Arabia, from January 7, 2016 to August 30, 2016. The questionnaire designed to calculate three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…Many still seek advice from cardiologists instead of referring to the guidelines before prescribing AP to patients [ 10 , 11 , 19 ]. This study showed that most microbiologists recommend adhering to the NICE guidelines, a finding that concurs with the Saudi Arabian study [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Many still seek advice from cardiologists instead of referring to the guidelines before prescribing AP to patients [ 10 , 11 , 19 ]. This study showed that most microbiologists recommend adhering to the NICE guidelines, a finding that concurs with the Saudi Arabian study [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…Dayer et al [ 10 ] included microbiologists and infectious disease specialists alongside dental specialists, cardiothoracic surgeons and cardiologists in their survey, while Soheilipour et al [ 19 ] (UK) and Rı’orda’in and McCreary [ 11 ] (Ireland) included cardiologists and dentists in their studies. In addition, Alhuzaimi et al [ 20 ] assessed the knowledge and practice attitudes of cardiologists and cardiothoracic surgeons towards the IE AP guidelines in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Эффективная профилактика ИЭ предполагает понимание этиологии, механизмов развития заболевания, оценку категорий пациентов, имеющих высокий риск его возникновения и доскональное знание самих превентивных мероприятий [21]. Несмотря на доступность и относительную простоту рекомендаций по АБП ИЭ, практические врачи, сталкивающиеся с группами больных, имеющими риск развития ИЭ, в целом недостаточно осведомлены о практических аспектах предупреждения заболевания, о чём свидетельствуют результаты исследований зарубежных коллег [22][23][24][25][26][27][28][29]. Целью представленного обзора является освещение различных аспектов ИЭ, касающихся, прежде всего, практических подходов к его профилактике.…”
Section: Introductionunclassified